The genuine works of Flavius Josephus - Josephus, Flavius 37-100 (W. Borradaile, 1824)
v. 1. Containing five books of the Antiquities of the Jews, to which are prefixed three dissertations.--v. 2. Containing six books of the Antiquities of the Jews.--v. 3. Containing five books of the Antiquities of the Jews.--v. 4. Containing four books of the Antiquities of the Jews. With the life of Josephus.--v. 5. Containing four books of the Jewish war.--v. 6. Containing three books of the Jewish war, &c, &c.